PENILAIAN DIMENSI PRODUCTIVE PEDAGOGIES MAHASISWA PENDIDIKAN BIOLOGI PADA PERKULIAHAN MICROTEACHING (Universitas PGRI Sumatera Barat, 2019)
Productive pedagogies describe the ability of an educator in implementing learning process. This ability should be owned by prospective teacher students in order to improve teacher professionalism in the future. This research was conducted to obtain an overview of productive pedagogies for students of biology education study programs. Productive pedagogies are measured based on three dimensions, namely intellectual quality, relevance, and mastery of the classroom environment for prospective teacher students who carry out teaching practices in the sixth semester of the microteaching lecture T.A 2018/2019. This research is a descriptive study conducted in January-May 2019. The assessment of productive pedagogies was measured by using a 5-point Likert scale questionnaire. Data acquisition was analyzed by converting low to very high values. Based on the overall dimensions measured through the questionnaire, the lowest average was found on the relevance dimension of 82.4 and the highest in the dimensions of intellectual quality was 84.95 with a very good category. The results showed that 74% of prospective teacher students argued that productive pedagogies were in the very high category.